K(ATP) channel mutation confers risk for vein of Marshall adrenergic atrial fibrillation - Olson, Timothy M (2007)
BACKGROUND: A 53-year-old female presented with a 10-year history of paroxysmal atrial fibrillation (AF), precipitated by activity and refractory to medical therapy. In the absence of traditional risk factors for disease, a genetic defect in electrical homeostasis underlying stress-induced AF was explored. INVESTIGATIONS: Echocardiography, cardiac perfusion stress imaging, invasive electrophysiology with isoproterenol provocation, genomic DNA sequencing of K(ATP) channel genes, exclusion of mutation in 2,000 individuals free of AF, reconstitution of channel defect with molecular phenotyping, and verification of pathogenic link in targeted knockout. DIAGNOSIS: K(ATP) channelopathy caused by missense mutation (Thr1547Ile) of the ABCC9 gene conferring predisposition to adrenergic AF originating from the vein of Marshall. MANAGEMENT: Disruption of arrhythmogenic gene-environment substrate at the vein of Marshall by radiofrequency ablation.